Analysis of the psychosocial component continuum of psychological adaptation-disadaptation in patients with a dermatological profile with different levels of vital threat - Skrebtsova Hanna (Psychiatry, Neurology and Medical Psychology, 2023)
Purpose: to investigate the state of psychosocial functioning as a component of the continuum of psychological adaptation - maladaptation in patients with a dermatological profile with diseases of various levels of vital threat, to develop, in the future, personalized psychocorrection programs for this category of patients. Contingent and research methods. On the basis of informed consent, in compliance with the principles of biomedical ethics and deontology, we examined 120 dermatological patients who were treated in three branches of the clinic “Dr. Zapolska Clinic” during 2020-2021, namely: 60 patients with non-vital dermatological diseases (seborrheic keratosis L82, condylomas A63.0, angiomas D18.0, pigmentation disorders L80), and 60 patients with dermatological diseases posing a vital threat (melanoma C43, basal cell carcinoma C44, skin carcinoma D04). The results. Both by integral indicators and by separate characteristics of socio-psychological adaptation/maladaptation, we found a general trend of the primary importance of the lack of adaptive resources and the secondary – nosospecificity features of dermatological pathology, in the formation of states of psychological maladaptation, which is manifested both in the clinical and psychological plane, and in the field of psychosocial functioning. These data are also consistent with the results of the study of the quality of life (QoL) of the examinees: the general trend of association between the level of QoL and the presence of signs of psychological maladjustment (PMA) was confirmed both for the integral criteria for the assessment of QoL and for 8 out of 10 evaluation parameters of QoL (levels of physical well-being and work capacity turned out to be nosospecificity, in contrast to all other parameters). The study confirmed our assumptions regarding the absence of a direct relationship between nosospecificity and vitality of a dermatological disease and the state of psychosocial functioning of an individual, especially in the context of adaptability and its resource base. The obtained results regarding the fact that dermatological patients without clinical signs of psychological maladjustment, regardless of the nosological affiliation of the main disease, have a sufficient resource of adaptability and use it in the field of social-psychological interaction, are predictable for us, but such that required scientific justification and proof. The issues of primary/secondary states of the resource base and adaptability at the clinical-psychological and psychosocial levels require further study. We assume that we are talking about the mechanisms of mutual influence of biological predisposition and psychological and psychosocial factors, the mosaic combination of which determines the resource capabilities of the individual regarding the constructive acceptance of the fact of the presence of a dermatological disease and the development of an adequate strategy for its mastery, regardless of the degree of vitality of the disease. Conclusion. The identified regularities should be considered when developing treatment-rehabilitation and psycho-prophylactic measures in patients with dermatological pathology with different levels of vital threat. measures in patients with dermatological pathology with different levels of vital threat